Boosting the hydrogen evolution activity of a Co–N–C electrocatalyst by codoping with Al. Issue 58 (23rd October 2019) - Zhou, Xiao; Yu, Haoran; Liu, Yang; Kong, Yong; Tao, Yongxin; Qin, Yong
Abstract : The electrocatalytic activity of Co–N–C catalyst toward hydrogen evolution reaction can be significantly boosted by codoping with Al. Abstract : Co, Al and N tri-doped graphene (CANG) was successfully fabricated via annealing N-doped graphene with Co and Al precursors. The material was characterized by scaning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Raman spectroscopy, physical adsorption, and X-ray photoelectron spectroscopy (XPS). It was found that the as-prepared CANG features a robust three-dimensional hierarchically porous structure. The contents of Co and Al can achieve the maximum value of 2.18 at% and 0.51 at% at the annealing temperature of 950 °C. Upon using the electrocatalyst for the hydrogen evolution reaction (HER), the CANG exhibited remarkable electrocatalytic performance in both acidic ( η 10 = 105 mV) and alkaline media ( η 10 = 270 mV), and outperforms Co, N-codoped graphene and Al, N-codoped graphene, respectively. In combination with the density functional theory (DFT) calculations, it was revealed that the introduction of the Al heteroatom can decrease the absolute value of hydrogen adsorption free energy (Δ G (H*)) of Co–N–C catalysts, thus greatly enhancing the HER activity. This discovery will provide new guidance to the design of advanced and inexpensive carbon materials for fuel cell, water-splitting and other electrochemical devices.